Development of Web-Based GIS for monitoring foreign direct investment inflow of Southeast Asia developing countries [2006-2016] / Siti Noor Nadiah Mohd Rafidi - Mohd Rafidi, Siti Noor Nadiah (2020)
Mapping and monitoring the Foreign direct investment inflow are deemed necessary especially for investor and government who implement sound policies. Thus, involve six parameters to analyse the increasing of FDI inflow. The aim of this study is to visualise the dynamic trend of Foreign Direct Investment in South East Asia towards countries performance and economic growth among the developing countries in South East Asia. This result of this study would provide a valuable explanation on the relationship between six parameters on the increasing of FDI inflow, thus, it would give relevant views to investors, researchers and government to have the awareness and get the idea what happen nowadays within investment filed by developing dynamic map using Web-Based GIS system